FINANCIAL INCLUSION IN THE INSURANCE MARKET OF UKRAINE: PREREQUISITES AND FACTORS OF FORMATION - Chvertko, L. A.; Korniienko, T. O.; Vinnytska , O. A. (The actual problems of regional economy development, 2022)
The purpose of the article is to substantiate the features, problems and factors of financial cluster formation in the insurance market of Ukraine and to outline the prospects for its development. Dialectical and abstract-logical methods, methods of system approach, observation, analysis, synthesis, induction, deduction, etc. were used during the research. The information base of the research is legislative and normative-legal acts; information of the Ministry of Digital Transformation of Ukraine, Ministry of Finance of Ukraine, the National Bank of Ukraine, State Statistics Service of Ukraine, the Motor (Transport) Insurance Bureau of Ukraine; scientific publications; internet sources. The importance of inclusive orientation of the insurance market of Ukraine, which is based on the economy of interaction of all its subjects, is emphasized, and the need to increase attention to the problems of insurance inclusiveness and increase the coverage of insurance services of all segments is substantiated. The economic and social imbalances that occur in the country and have a negative impact on the process of wide involvement of potential customers in the insurance system have been identified. It is substantiated that the determinants of the formation of financial inclusion in the insurance market of Ukraine are the provision of appropriate levels of digital and financial literacy of the population. The importance of intensifying the use of digital technologies by insurers for positive changes in the development of the insurance business and ensuring the inclusiveness of insurance products and services has been proved. The scientific novelty is to assess the conditions for ensuring financial inclusion in the field of insurance in Ukraine and justify the need to develop effective approaches to ensure the inclusive development of the domestic insurance market in today's challenges. The practical significance of the obtained results lies in the possibility of using theoretical conclusions and practical recommendations to increase the coverage of insurance products and services by creating appropriate conditions for attracting the general public and business.